PERLINDUNGAN HUKUM BAGI KONSUMEN PADA TRANSAKSI ASET KRIPTO - Alisya Nur Hidayah Rizki (2022)
This study aims to find out how crypto asset transactions are carried out based on current regulations. As well as analyzing how the legal protection for consumers in crypto asset transactions. In this study, the theory of preventive and repressive legal protection is used. Regulations regarding the implementation of the physical market for crypto assets and also making crypto into an asset that can be traded on the futures exchange have also been set by the government. It should also be noted that the most recent regulation regarding crypto asset transactions has been enacted, namely BAPPEBTI Regulation No. 8 of 2021, but the legal basis used in this research still refers to the previous regulation, namely BAPPBETI Regulation No. 5 of 2019. The prospects offered by these digital products can be said to be promising. However, keep in mind that crypto assets include assets that have a high risk due to their volatile prices. The results of this study indicate that the implementation of crypto asset transactions in Indonesia is currently running smoothly and also forms of legal protection for consumers have been fulfilled. One form of preventive protection in this case is to apply the principles of good corporate governance and evidence of repressive protection, one of which is the availability of BAKTI as an agency appointed by BAPPEBTI to resolve disputes that occur in crypto asset transactions.